A Humboldtian Approach to Mountain Conservation and Freshwater Ecosystem Services - Callisto, Marcos; Solar, Ricardo; Silveira, Fernando A. O.; Saito, Victor S.; Hughes, Robert M.; Fernandes, G. Wilson; Gonçalves-Júnior, José F.; Leitão, Rafael P.; Massara, Rodrigo L.; Macedo, Diego R.; Neves, Frederico S.; Alves, Carlos Bernardo M. (Frontiers in Environmental Science, 2019)
Tackling complex environmental issues requires transdisciplinary solutions that cannot be achieved, unless we integrate scientific disciplines and communicate science directly with civil society actors, decision-makers, and stakeholders. Alexander von Humboldt offered an approach to integrate knowledge across disciplines aiming to broadly understand human-environmental issues, yet current scientific practices largely ignore that holistic transdisciplinary approach. Here, we develop a conceptual framework for sustaining mountain environmental integrity and securing their ecosystem services based on transdisciplinarity. We use headwater systems located in old tropical mountains as examples of meta-ecosystems because they supply water for multiple human uses and are home to disproportionately high levels of species richness and endemism. We describe the vulnerability of mountains to global changes in the Anthropocene and discuss difficulties in implementing sustainable development goals for them. Specifically, we indicate the importance of mountains to human water supplies and the conflicts between anthropogenic disturbances and riparian stream meta-ecosystems for providing ecosystem services particularly failures. We also argue that the interplay between academia and other sectors of society must improve and increase the permeability of scientific knowledge into policy- and decision-making, which is crucial for improving natural resource management and sustaining ecosystem services. We argue that the prioritization of tropical montane headwater systems is a feasible, desirable and strategic issue to be included in the global sustainability agenda. Failure to implement sustainable development goals in global mountains is likely to continue resulting in catastrophic events with harsh consequences for both humans and global biodiversity.